Implications of global climate change on cow parsnip in Colorado: from flowering phenology to multitrophic interactions - Smith, Brittany N., author; Ode, Paul J., advisor; Bjostad, Louis, committee member; Seshadri, Arathi, committee member (Colorado State University. Libraries, 2019)
Plants play a central role in structuring nearly all terrestrial communities and providing ecosystem services. As ectothermic organisms, the synchronization of plant and insect life history events (phenology) are strongly dependent on temperature and precipitation, two of the major components of climate change. Plants can serve as indicator species for how climate change might alter community composition that in turn contributes to ecosystem and landscape stability. I investigated elevation as a proxy for climate change from ten spatially separate Colorado populations of cow parsnip Heracleum maximum Bartram (Apiaceae) in both 2017 and 2018. I studied, plant flowering phenology and plant trait measurements that attributed to plant fitness measures (seed production and weight). Additionally, I investigated floral visitors in association with flowering phenology and how the presence or absence of parsnip webworm Depressaria radiella Goeze (Lepidoptera: Depressariidae) impacted pollinators visiting plants. I found that elevation does not clearly explain phenological differences amongst H. maximum plants in high elevations (>2600m), yet insect diversity decreases as elevation increases. Additionally, D. radiella presence increases plant seed production, and secondary plant umbels compensate for consumed primary umbel flowers and fruit. I also found that male flowers with pollen or female flowers with nectar are not significantly different from each other in regard to insect families that visit them. Lastly, both abiotic conditions and biotic plant-insect interactions may contribute to multitrophic community assemblages under warming temperatures.
Keywords: cow parsnip; phenology; Depressaria radiella; multitrophic interactions; Heracleum; Apiaceae